2006
DOI: 10.1021/jp065635k
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Distribution Control by Polymers:  Aggregates versus Nonaggregates

Abstract: Aggregation states of both stabilized (by organic ligands) and nonstabilized nanoparticles have been studied in solutions, on plain surfaces, and within the polyelectrolyte multilayer capsules to provide control over formation of aggregates and their uniformity. Adsorption of nanoparticles could be performed either simultaneously with polymers to achieve their uniform (nonclustered or nonaggregated) distribution or without polymers for obtaining nonuniform (clustered or aggregated) distribution. Nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
115
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 77 publications
(175 reference statements)
2
115
1
Order By: Relevance
“…This stronger interaction is attributed to decreasing the distances between neighboring nanoparticles as their concentration in the film increases. Results reported in this work extend our previous work on controlling the distribution of nanoparticles on spherical microcapsules [90,91] to planar LbL films. It can be noted that adsorption of one polyelectrolyte layer sequentially with nanoparticles [92] can be used for further increase of density of nanoparticles.…”
Section: Gold Nanoparticles On Polyelectrolyte Multilayerssupporting
confidence: 83%
See 1 more Smart Citation
“…This stronger interaction is attributed to decreasing the distances between neighboring nanoparticles as their concentration in the film increases. Results reported in this work extend our previous work on controlling the distribution of nanoparticles on spherical microcapsules [90,91] to planar LbL films. It can be noted that adsorption of one polyelectrolyte layer sequentially with nanoparticles [92] can be used for further increase of density of nanoparticles.…”
Section: Gold Nanoparticles On Polyelectrolyte Multilayerssupporting
confidence: 83%
“…The position of the peak depends on and can be controlled by the distance between nanoparticles or their aggregates. It can be noted that control of the distribution both at high [90] and low [91] concentrations of nanoparticles enables tailoring optical properties.…”
Section: Gold Nanoparticles On Polyelectrolyte Multilayersmentioning
confidence: 99%
“…[26][27][28] Considerable progress was achieved in the use of laser irradiation for microcapsule opening. 22,23 Usually, metal nanoparticles [19][20][21][22][23] or dyes 19 are used to provide microcapsule shell sensitivity to laser radiation. Our research has recently demonstrated that it is possible to release encapsulated materials inside living cells from laser-sensitive capsules.…”
Section: Introductionmentioning
confidence: 99%
“…22 It was also established, that the use of aggregates composed of nanoparticles decreases the laser intensity, necessary for microcapsule opening and release of encapsulated substances. 23 Some hurdles in use of lasers for microcapsules opening are connected with a local effect of laser irradiation. Iron oxide nanoparticles present in the capsule shell can be used to concentrate and transfer the microcapsules by magnetic field 10 and to influence the distribution of gold nanoparticles in the nanocomposite shell during their preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, polymer adsorption plays a major role in the control of particle size during polymer-mediated particle synthesis and on the characteristics of the particle suspensions in the polymer solutions. [18][19][20][21][22][23][24][25] Moreover, the adsorption of polymers on metallic substrates can also serve to modify and pattern the chemical properties of the surfaces according to the chemical nature of the polymer, the extent and nature of the metallic particle/polymer interfacial interactions, and the resulting surface morphology of the adsorbed layer. In order to provide additional degrees of freedom that would enable the control of structural properties of the adsorbed layer, recent work utilized systems that include block copolymers having blocks with dissimilar chemical features.…”
Section: Introductionmentioning
confidence: 99%